Cereal-maize vs. legume-maize double-cropping: Impact on crop productivity and nitrogen dynamics under flood-irrigated Mediterranean conditions - María Alonso-Ayuso; Samuel Franco-Luesma; Victoria Lafuente; Ana Bielsa; Jorge Álvaro-Fuentes (Journal of Agriculture and Food Research)
Double-cropping is an interesting diversification strategy to increase profitability and sustainability. Besides, by including legumes, it may reduce the N inputs dependency. However, its management with flood irrigation can be challenging. The was the evaluation of the impact of two double-cropping and different nitrogen (N) rates on productivity and N dynamics under flood irrigation. Two double-cropping (barley-maize; pea-maize) and three N rates (unfertilized, 0N; medium: MN; high rate, HN) were evaluated in a field experiment located in NE Spain during two years. In barley-maize, N rates were 0, 125 and 250 kg N ha−1, and 0, 200 and 400 kg N ha−1 for barley and maize phases, respectively. In pea-maize, pea did not receive N, and the MN and HN rates in the maize were reduced (150 and 350 kg N ha−1, respectively).Crop productivity and N uptake were evaluated. The economic return and N use efficiency (NUE) were calculated. Soil inorganic N (Nmin) was measured after harvest.The pea-maize double-cropping allowed the saving of N fertilizer without yield penalties. Besides, a pre-crop effect of pea in the maize yield was observed. Regarding the cropping system, pea-maize obtained a higher economic return the first year. Besides, the economic return was higher the first year, due to crop penalties. In general, NUE was greater in 0N, and no differences were observed between fertilized treatments. Soil Nmin after pea/barley was higher the first year, coincident with a higher productivity. After maize harvest, the barley-maize led to larger residual Nmin.Therefore, in this study, pea-maize allowed a reduction in the N rate, showed greater potential to increase the economic return and reduced the N leaching risk. However, crop yield penalties associated with flood-irrigation, indicate that farmers should be aware of facing a more challenging management or consider other irrigation method to ensure profitability.